Conhecendo o Bairro São Francisco de Assis - Paulino, Tereza de Fátima; Felix, Giane; Fernandes, Marta Oliveira Cordeiro; Bordinhão, Andréia Chiozoni; Carraro, Márcia Regina Simpione (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER ´PDF